Surface structural features and optical analysis of nanostructured Cu-oxide thin film coatings coated via the sol-gel dip coating method. Issue 10 (July 2019) - Amri, Amun; Hasan, Kamrul; Taha, Hatem; Rahman, M. Mahbubur; Herman, Syamsu; Andrizal,; Awaltanova, Ella; wantono, I.; Kabir, Humayun; Yin, Chun-Yang; Ibrahim, Khalil; Bahri, Syaiful; et al.
Abstract: Nanostructured thin film coatings of copper oxide (Cu-oxide) were investigated to determine their physical structure, surface morphology, surface electronic bonding states, and optical properties. The Cu-oxide had been coated onto reflective aluminum substrates via a facile one-step sol–gel dip-coating route using a copper nitrate precursor. Characterizations were conducted using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), and ultra-violet visible (UV–Vis) spectroscopic methods, and representative sol-gel reactions using copper nitrate precursor were proposed. The XPS spectra confirmed the presence of copper oxide elements. Further exploration of the Cu2 p 3/2 peak in XPS spectra revealed that the electronic structure of the copper component consisted of tetrahedral Cu(I) and octahedral Cu(II) with the presence of octahedral Cu(II) enabling coatings to have high absorption levels across the solar spectrum. The deconvolution of the O1 s spectra exhibited three curve-fitting components: the lattice O 2−, surface oxygen, and subsurface O − species. FESEM results showed that the coating surface was an agglomerated copper oxide nanoparticles structure forming a porous structure. The optical band-gap of Cu-oxide thin film coatings, via the Tauc plot, was 2.7 eV.